Exploring the Needs of an ESP Course in the Music Education Department - Fidianingsih, Ambar (Universitas Nurul Jadid, 2025)
English for specific purposes has been highlighted for its importance in enhancing specialized language skills for university students, including those in the music education department. This study aims to determine music education students’ characteristics, target needs, and learning needs for an ESP course. The data were collected by distributing a questionnaire to students of the music education department and conducting an interview with a graduate of the music education department. The findings show the music education students’ characteristics, what they need in the target situation, and what they need to learn in the ESP course. Most students had positive attitudes towards English, realized the importance of English, and had been using English in some daily activities. Regarding the target needs, most students wanted the ESP course to help them learn English in music contexts and learn music from various English resources. Related to learning needs, some points about materials delivery and assessment were found. The results of this study can be used as the foundation for developing an “English for music education students” course.